2002
DOI: 10.1038/sj.bjp.0704675
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of human penile smooth muscle tone byprostanoid receptors

Abstract: 1 We have characterized the prostanoid receptors involved in the regulation of human penile arterial and trabecular smooth muscle tone. 2 Arachidonic acid induced relaxation of human corpus cavernosum strips (HCCS) that was blocked by the cyclo-oxygenase inhibitor, indomethacin, and augmented by the thromboxane receptor (TP) antagonist, SQ29548, suggesting that endogenous production of prostanoids regulates penile smooth muscle tone. 3 TP-receptors mediate contraction of HCCS and penile resistance arteries (HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
71
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 38 publications
4
71
0
Order By: Relevance
“…11 Concerning expression of EP receptor in human corpus cavernosum, there are some previous reports using pharmacological method. Angulo et al 12 reported that EP2 receptor and/or EP4 receptor were related to relaxation of smooth muscle in human corpus cavernosum. In this pharmacological experiment, butaprost was used as the EP2 selective agonist by this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Concerning expression of EP receptor in human corpus cavernosum, there are some previous reports using pharmacological method. Angulo et al 12 reported that EP2 receptor and/or EP4 receptor were related to relaxation of smooth muscle in human corpus cavernosum. In this pharmacological experiment, butaprost was used as the EP2 selective agonist by this study.…”
Section: Discussionmentioning
confidence: 99%
“…13 Therefore, it is not clear as to which one of EP receptor subtype (EP2 or EP4) works predominantly in relaxation of human corpus cavernosum by this report. 12 In addition to butaprost, sulprostone, which has agonistic activity for both EP1 and EP3, was used in this report, and did not lead to contraction of human corpus cavernosum. 12 Moreland et al 14 reported that human corpus cavernosum tissues and cultured smooth muscle cells express EP1, EP2 and EP3 receptors by RNase protection assay and pharmacological methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Of these eicosanoids, only PGE 1 has been reported to relax penile cavernosal smooth muscle. [7][8][9][10] Further, arachidonic acid, the precursor of PGE 2 , can relax human corpus cavernosum (HCC) smooth muscle in the presence of thromboxane receptor antagonists, a process blocked by the prostaglandin G/H synthase inhibitor indomethacin. 10 Prostaglandin E can bind to several different subtypes of EP receptors.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Further, arachidonic acid, the precursor of PGE 2 , can relax human corpus cavernosum (HCC) smooth muscle in the presence of thromboxane receptor antagonists, a process blocked by the prostaglandin G/H synthase inhibitor indomethacin. 10 Prostaglandin E can bind to several different subtypes of EP receptors. EP1 (Ga q11 -coupled) and EP3 (Ga i/ocoupled) receptors can potentially mediate trabecular smooth muscle contraction, while EP2 and EP4 (Ga s -coupled) may mediate trabecular smooth muscle relaxation via different signal transduction pathways.…”
Section: Introductionmentioning
confidence: 99%